2019
DOI: 10.1002/1873-3468.13538
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to Pb2+ perturbs ChREBP transactivation and coerces hepatic dyslipidemia

Abstract: Dysregulated hepatic de novo lipogenesis contributes to the pathogenesis of nonalcoholic fatty liver disease in both humans and rodents. Clinical evidence suggests fatty liver to have a positive correlation with serum lead (Pb2+) levels. However, an exact mechanism of Pb2+‐induced fatty liver progression is still unknown. Here, we show that exposure to Pb2+ regulates ChREBP‐dependent hepatic lipogenesis. Presence of Pb2+ ions within the hepatocytes reduces transcript and protein levels of sorcin, a cytosolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Indeed, environmental exposures such as heavy metals have been involved even though results are conflicting and possible mechanisms remain unclear [89]. Authors found that Pb2+ exposure could be a lethal disruptor of lipid metabolism in hepatocytes, and highlighted sorcin (a cytosolic adaptor partner of carbohydrate responsive element binding protein (ChREBP)-dependent hepatic lipogenesis) as a novel therapeutic target against Pb2+-induced hepatic dyslipidemia [90]. Hepatic de-novo lipogenesis (DNL) is a metabolic process proposed in the pathogenesis of T2DM, with multiple enzymes involved in this process [91].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…Indeed, environmental exposures such as heavy metals have been involved even though results are conflicting and possible mechanisms remain unclear [89]. Authors found that Pb2+ exposure could be a lethal disruptor of lipid metabolism in hepatocytes, and highlighted sorcin (a cytosolic adaptor partner of carbohydrate responsive element binding protein (ChREBP)-dependent hepatic lipogenesis) as a novel therapeutic target against Pb2+-induced hepatic dyslipidemia [90]. Hepatic de-novo lipogenesis (DNL) is a metabolic process proposed in the pathogenesis of T2DM, with multiple enzymes involved in this process [91].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…i.p of D-glucose. Insulin sensitivity was examined by the insulin tolerance test (ITT) in 6 hr fasted mice challenged with 0.5 units/kg ip insulin (39). The results were expressed by calculating the percentage of area under the glucose and basal insulin curve (AUC) using GraphPad Prism.…”
Section: Metabolic Parameters Analysis-mentioning
confidence: 99%
“…Following two PBS washes, cells were stained with Bodipy (2µM) for 30mins at 37 0 C. Cells were mounted using mounting media (Sigma) following three PBS washes and later visualized on a confocal microscope (A1+, Nikon) and representative images have been presented. Liver tissues were embedded in Tissue-Tek, frozen sections were then processed for ORO staining using a routine method 20 . Images were captured using Nikon Eclipse TS 100 confocal microscope.…”
Section: Nuclear Localization Analysis Of Chrebpmentioning
confidence: 99%
“…Significant interaction sites of NF-κB were found on the promoter at 75 base pairs J o u r n a l P r e -p r o o f upstream to the transcription start site. Chromatin immunoprecipitation to assess occupancy of phosphorylated p65 along with co-repressor on sorcin promoter was performed as described previously 20 . Primers enriching the domain containing NF-κB consensus (-313bps to -22bps) were designed using the EPD tool.…”
Section: Nuclear Localization Analysis Of Chrebpmentioning
confidence: 99%
See 1 more Smart Citation